The Experience of Existential Connection as a Naturalistic Concept for Spirituality - Braun, Ricardo (2017)
In this paper, I propose the use of the term existential connection experience as a possible replacement of the term spirituality, to avoid religious connotations and to better represent a naturalistic fuller view of human experience. I discuss the current debate on the best term to represent the phenomenon associated to connections of the human subject with his/her own existence and their situated existence with the universe. This term, which should become a concept represents the relationship of belonginess and commitment with reality. Moreover, the existential component refers to the traditional topics dealt with by philosophical existentialism.